-2(1+6x)-3=

Simple and best practice solution for -2(1+6x)-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(1+6x)-3= equation:


Simplifying
-2(1 + 6x) + -3 = 0
(1 * -2 + 6x * -2) + -3 = 0
(-2 + -12x) + -3 = 0

Reorder the terms:
-2 + -3 + -12x = 0

Combine like terms: -2 + -3 = -5
-5 + -12x = 0

Solving
-5 + -12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -12x = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -12x = 0 + 5
-12x = 0 + 5

Combine like terms: 0 + 5 = 5
-12x = 5

Divide each side by '-12'.
x = -0.4166666667

Simplifying
x = -0.4166666667

See similar equations:

| 3x+12=69 | | 11=2(w-2)+2w | | 10b-10=9b | | -5(9p-4)= | | 48n^2-6=-42n | | f^2+g^2=2fg | | -10x+3=-17 | | 3x-9=10x-30 | | 63=3u | | 2x+12=2x-19 | | 3e=27 | | 1/5=10/50 | | 3-18+4m=m | | 10=v-9 | | b-1+4=b-1 | | 16-16xsquared=0 | | 115+24x-5=90 | | 100*y=2.2973 | | 10r+2=3(r+4) | | y-9=-7 | | 6+15n=17n+26 | | m+9=91 | | 4(x+6)=2(7x+1) | | 440=3(w-60)+2w | | x-.22x=506.61 | | 3m+2n=-2 | | 4q=84 | | 11x+5x-103=105 | | 49k+105=1323-21k | | 4p=86 | | 4xb=52 | | Y^2-79=90 |

Equations solver categories